11th AIAA/ISSMO Multidisciplinary Analysis and Optimization Conference 2006
DOI: 10.2514/6.2006-6950
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Family Design Using Decomposition-Based Methods

Abstract: This paper explores the use of decomposition-based methods for aircraft family design. The traditional approach in multidisciplinary design optimization is to decompose a problem along disciplinary lines. For aircraft family design problems, a more natural approach is decomposition by individual aircraft. This decomposition facilitates the concurrent development of several aircraft variants, providing substantial autonomy to individual aircraft development programs. Two decomposition-based methods are applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…It has been most frequently applied to design problems in the field for which it was developed, the automotive industry [175,176,177,178,29,179,180,181]. However, it has also proved useful in aircraft design [182,150,54] and building design [23].…”
Section: F Analytical Target Cascading (Atc)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been most frequently applied to design problems in the field for which it was developed, the automotive industry [175,176,177,178,29,179,180,181]. However, it has also proved useful in aircraft design [182,150,54] and building design [23].…”
Section: F Analytical Target Cascading (Atc)mentioning
confidence: 99%
“…Examples include the design of launch vehicles [39], rocket engines [40], satellite constellations [147], flight trajectories [72,148], and flight control systems [149], as well as the preliminary design of complete aircraft [17,18] and aircraft family design [150]. Beyond aerospace engineering, CO has been applied to problems involving automobile engines [28], bridge design [22], and railway cars [26], and even the design of a scanning optical microscope [27].…”
Section: Collaborative Optimization (Co)mentioning
confidence: 99%
“…A Multi-Objective Particle Swarm Optimization (MOPSO) method was proposed by Seng Ki et al [8]. Moreover, James et al and Dongwook et al suggested an evolutionary method and data mining technique for a family of aircraft design [9,10]. They assumed values for the requirements needed for the market purposes, which often differed from actual market requirements.…”
Section: Jonathan Et Al Utilized the Generation Of A Paretomentioning
confidence: 99%
“…Many researchers studied techniques for derivative design. These research efforts considered the whole set of design variables and designed the baseline and derivatives simultaneously [1][2][3][4][5][6][7][8][9][10]. Richard et al, Robert et al, and Deepak et al identified the important parameters for the family design by applying the market requirement analysis [1, 2, and 3]…”
Section: Introductionmentioning
confidence: 99%
“…The product platform and its corresponding family of products were simultaneously optimized using a genetic algorithm while considering levels of platform [13, 14, and 15]. Furthermore, James Allison et al (2006), and Dongwook Lim and Dimitri N. Mavris (2007) researched other methods in order to design an aircraft family [16,17]. The previous researchers considered the whole set of design variables simultaneously in order to design the baseline and its derivatives together.…”
Section: Derivative Designmentioning
confidence: 99%